Personality on Green Consumer Behaviour - Cholilawati,; Made Putrawan, I; Nadiroh, (International Journal of Psychosocial Rehabilitation, 2020)
In previous studies, it was said that in general, pro-environment behavior is related to personality, whereas other studies have shown that personality is also associated with certain pro-environment attitudes. Therefore, the purpose of this study is to determine the relationship between personality and green consumer behavior. This research uses the survey method using the correlation analysis technique. The target population in this survey is the Central Jakarta District Code, and the study population is 8 Central Jakarta District Districts. The population in this survey is late adolescence, which is adolescents aged around 17-20 years. As a sampling unit are teenagers who are doing their activities in modern shopping centers (malls). The sampling technique is done by purposive sampling and incidental sampling methods in adolescents who are in the mall location. From the testing of the significance of the coefficient obtained, it appears that the regression coefficient is significant and that there is a positive influence on the independent variable X1 (personality) on the dependent variable Y (green customer behavior).